Bridget Jones [compact disc, unabridged] : mad about the boy - Fielding, Helen, 1958- (Books on Tape, 2013)
With her hotly anticipated third installment, Bridget Jones: Mad about the boy, Fielding introduces us to a whole new, enticing phase of Bridget's life, set in contemporary London, including the challenges of maintaining sex appeal as the years roll by, and the nightmares of drunken texting, the skinny jean, the disastrous e-mail cc, total lack of Twitter followers, and TVs that need ninety buttons and three remotes to simply turn on.